2012
DOI: 10.1371/journal.pone.0039179
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Blockage Reverses Immune Dysfunction and Hepatitis B Viral Persistence in a Mouse Animal Model

Abstract: Persistent hepatitis B viral (HBV) infection results in chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC). Recent studies in animal models of viral infection indicate that the interaction between the inhibitory receptor, programmed death (PD)-1, on lymphocytes and its ligand (PD-L1) play a critical role in T-cell exhaustion by inducing T-cell inactivation. High PD-1 expression levels by peripheral T-lymphocytes and the possibility of improving T-cell function by blocking PD-1-mediated sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 26 publications
7
87
0
1
Order By: Relevance
“…The upregulation of PD-1 is a typical sign of T cell exhaustion. Previous studies indicated that elevated expression of PD-1 has a close relationship with immune defects in chronic viral infection, tumor, and aging [21-24], and blockade of PD-1 pathways was observed to restore the T cell functional defects in both chronic virus infection and tumor models [21, 22, 24-27]. In addition, T cell exhaustion appears to be correlated with a higher antigen load, persistent exposure to antigens, and decreased specific CD4 + T cells [28].…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of PD-1 is a typical sign of T cell exhaustion. Previous studies indicated that elevated expression of PD-1 has a close relationship with immune defects in chronic viral infection, tumor, and aging [21-24], and blockade of PD-1 pathways was observed to restore the T cell functional defects in both chronic virus infection and tumor models [21, 22, 24-27]. In addition, T cell exhaustion appears to be correlated with a higher antigen load, persistent exposure to antigens, and decreased specific CD4 + T cells [28].…”
Section: Introductionmentioning
confidence: 99%
“…Liver tolerance can be observed even during chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infection, which usually induces CTL dysfunction and impaired responses to vaccination, resulting in ∼350 million chronic HBV-carrier people worldwide; thus, it is a major global health problem (2). In HBV-carrier humans or mice, the number and function of HBV-specific CD8 + T cells are gradually reduced with impaired IFN-g and TNF-a production as well as upregulation of coinhibitory factors, such as PD-1; together, these changes are also characteristic of CD8 + T cell exhaustion (3)(4)(5). Previous studies showed that regulatory T cells (Tregs) might suppress the priming, activation, and proliferation of HBV-specific CD8 + T cells, and that Treg depletion restored T cell function and accelerated HBV clearance in patients and HBV-carrier mice (6).…”
mentioning
confidence: 99%
“…Zhang y colaboradores encontraron que en pacientes con VHB el 70% de los linfocitos T específicos para el virus eran positivos para PD-1 (54). Varios estudios han sido publicados al respecto, uno de ellos realizado en ratones con infección crónica por VHB demostró que los anticuerpos anti-PD-1 lograron revertir la disfunción inmune y ayudaron en cierta medida a depurar el virus (60% de negatividad para HBsAg en comparación con 20% en los controles) (55). Actualmente los anticuerpos anti PD-1 se utilizan para el cáncer y se encuentran en ensayos clínicos para la hepatitis crónica por VHC (56).…”
Section: Bloqueo De Señales Inmunoinhibidoras (Pd-1)unclassified